Diagnostic Accuracy of Ultrasound in Predicting Extrathyroidal Extension and Its Relation to Body Mass Index in a North American Population - Mahmoud Omar; Abdallah S. Attia; Peter P. Issa; Bryce R. Christensen; Kavin Sugumar; Ahmed Alnahla; Deena Hadedeya; Hosam Shalaby; Neel Gupta; Mohamed Shama; Eman Toraih; Emad Kandil (Biomedicines, 2022)
Detection of extrathyroidal extension (ETE) in patients with papillary thyroid carcinoma (PTC) influences treatment plan and surgical aggressiveness. Ultrasound (US) is the long-standing preoperative imaging method of choice. Recent literature from Asia suggests US accuracy to be influenced by patient characteristics, such as body mass index (BMI). Here, we examine the effect of BMI on the accuracy of US at a North American tertiary referral center. A total of 204 PTC-confirmed patients were retrospectively read by a radiologist blinded to surgical pathology findings. The radiologist recorded multiple sonographic features, including ETE, loss of echogenic capsule, nodule vascularity, capsular abutment, and bulging of contour. When considering all patients, the ultrasonographic feature with the best overall performance was loss of echogenic capsule (diagnostic odds ratio (DOR) = 4.48, 95% confidence interval (CI) = 1.86–10.78). Sub-group analysis by patient BMI found that area under the curve (AUC) for sonographic features was greater in non-obese BMI patients (0.71 ± 0.06) when compared with obese patients (0.43 ± 0.05; p = 0.001). Overall, US diagnostic performance was significantly better in non-obese (DOR = 3.70, 95%CI = 1.53–8.94) patients when compared to those who were obese (DOR = 1.12, 95%CI = 0.62–2.03; p = 0.03). Loss of the echogenic capsule did not differ between the two cohorts with respect to DOR (p = 0.51), specificity (p = 0.52), or sensitivity (p = 0.09). Our work suggests that the diagnostic value of ETE detection by US is impaired in obese patients. Considering that loss of the echogenic capsule did not differ with respect to diagnostic performance, specificity, nor sensitivity between non-obese and obese patients, it could be considered the most important predictor of US-determined ETE.